Sources and Formation of Atmospheric Nitrate Over China–Indochina Peninsula in Spring: A Perspective From Oxygen and Nitrogen Isotopic Compositions Based on Passive Air Samplers - Wang, Xiao; Li, Jun; Tian, Chongguo; Zong, Zheng; Liu, Qilu; Jiang, Hongxing; Li, Tingting; Li, Jing; Jiang, Haoyu; Zhao, Shizhen; Zhang, Gan (Frontiers in Environmental Science, 2022)
The formation processes and potential sources of particulate nitrate can be revealed by nitrogen (δ15N-NO3−) and oxygen (δ18O-NO3−) isotopes; however, the linkage and comparative information over a large scale is limited. In this work, the feasibility of using quartz wool disk passive air samplers (Pas-QW) to identify and quantify the nitrate concentrations and its isotopic compositions was demonstrated. The results of simultaneous sampling campaign from March to June showed that the NO3− concentration was largely attributed to the development of the regional economies. The regional distribution of δ15N-NO3− values was due to the source changes. The decreasing trend of δ18O-NO3− values with latitude from south to north was mainly a combination of oxygen isotopic fractionation of oxidant induced by natural factors and anthropogenic changes of O3 concentrations. Coal combustion (CC) and mobile sources (MS) have a significant contribution to NOx in the typical urban agglomerations, while high contribution from biomass burning (BB) and biogenic soil emission (BS) were mainly in areas with high natural productivity and intensive agricultural activities. By allowing simultaneously monitoring at multiple sites and over extended periods, passive sampling complements existing techniques for studying nitrate aerosol, and the results can provide a reference for the spatial distribution of its sources and formation in China-Indochina Peninsula (CICP).